Identification of factors to reduce the energy costs of dispersing in jets - Gorobets, L.; Verhorobina, I.; Biletskyi, V. S.; Krivenko, A.; Grishchenko, M.; Bulakh, O. (PC Technology Center, 2020)
This paper reports the operational indicators for industrial-sized jet grinding plants (JGP). The dependences of specific energy consumption on productivity have been generalized. The technological patterns in the working process were considered in terms of reducing energy costs using the operation of gas-jet and steamjet mills at the Vilnohirsk Mining and Metallurgical Plant (VMMP) involved in crushing zircon to 60 μm as an example. The acoustic activity in the grinding area has been studied relative to the concentration of μ and in combination with the technological assessment of the mill’s performance. A broadband piezo sensor was used in the assessment of acoustic emission (AE). It is shown that the acoustic activity of the grinding zone contains information about the effects of dispersion and energy costs for grinding, which makes it possible to estimate and minimize the specific energy costs. It has been established that the principal factors of JGP energy intensity are the initial temperature of the energy carrier, which sets the speed of the jet, and the concentration of solid phase in the jet, which changes the effects of dispersing. A technique has been proposed for the current assessment of energy costs in the working process of dispersion based on the experimental acoustic data and a pattern of the acoustic dimensional effect.The estimated acoustic indicators of the energy cost of a jet mill for the conditions of VMMP were derived.
Keywords: jet mill; dispersion; energy carrier temperature; solid-phase concentration; acoustic activity